ANALISIS SISTEM AGRIBISNIS TERNAK KAMBING (Studi Kasus pada Usaha Peternakan Prima Aqiqah di Kota Bandar Lampung) - Megi Adi Guna; Dyah Aring Hepiana Lestari; Ani Suryani (Lampung University, 2020)
This research aims to analyze procurement system of production facilities that are appropriate to six preciseness (on time, place, quality, quantity, type, and price), income from the goat livestock business, added value of goat processed products, the marketing channels of goat livestock, and supporting servicesfor goat farming. This research uses a case study method carried out at Prima Aqiqah Farm in Bandar Lampung City. This location is chosen purposively as consideration that Prima Aqiqah Farm is a goat breeding business that processes goat products. Data were collected in April—May 2017 and analyzed usinga qualitative and quantitative desctiptive analysis. The results of this research shows that the procurement of production facilities for the goat farm business at Prima Aqiqah Farm has fulfilled the six preciseness. The goat of Prima Aqiqah Farm is profitable and feasible because R/C value ≥ 1. Therefore, processed products at Prima Aqiqah Farm have positive added value. The marketing channel for goat livestock products has two marketing channels, namely direct marketing channels to consumers and indirect. While processed productsonly have one marketing channel which is a direct marketing channel to consumers. Supporting service institutions that support the business activities of goats are financial institutions, transportation facilities, and information and communication technologies that provide benefits for Prima Aqiqah Farm.Key words : agribusiness system, aqiqah, goat